CRISPR–Cas9-mediated genome editing in apple and grapevine. Issue 12 (December 2018) - Osakabe, Yuriko; Liang, Zhenchang; Ren, Chong; Nishitani, Chikako; Osakabe, Keishi; Wada, Masato; Komori, Sadao; Malnoy, Mickael; Velasco, Riccardo; Poli, Michele; Jung, Min-Hee; Koo, Ok-Jae; et al.
Abstract The CRISPR–Cas9 genome-editing tool and the availability of whole-genome sequences from plant species have revolutionized our ability to introduce targeted mutations into important crop plants, both to explore genetic changes and to introduce new functionalities. Here, we describe protocols adapting the CRISPR–Cas9 system to apple and grapevine plants, using both plasmid-mediated genome editing and the direct delivery of CRISPR–Cas9 ribonucleoproteins (RNPs) to achieve efficient DNA-free targeted mutations in apple and grapevine protoplasts. We provide a stepwise protocol for the design and transfer of CRISPR–Cas9 components to apple and grapevine protoplasts, followed by verification of highly efficient targeted mutagenesis, and regeneration of plants following the plasmid-mediated delivery of components. Our plasmid-mediated procedure and the direct delivery of CRISPR–Cas9 RNPs can both be utilized to modulate traits of interest with high accuracy and efficiency in apple and grapevine, and could be extended to other crop species. The complete protocol employing the direct delivery of CRISPR–Cas9 RNPs takes as little as 2–3 weeks, whereas the plasmid-mediated procedure takes >3 months to regenerate plants and study the mutations. This protocol provides approaches for applying the CRISPR–Cas9 system for genome editing in apple and grapevine plants, using both plasmid-mediated delivery of components and direct delivery of CRISPR–Cas9 ribonucleoproteins.